Estimating the Cost of Equity in Emerging Markets: A Case Study (American Journal of Management, 2017)
A firm’s weighted average cost of capital is an integral component in capital budgeting decisions and in assessment of the firm’s enterprise and equity value. Estimation of the cost of equity is a key component in determining the overall cost of capital. The calculation of the cost of equity for U.S. based corporations is relatively straightforward and is most often estimated as a function of the U.S. risk-free rate, the firm’s beta value, and an estimate of the average risk premium associated with equity investments compared to risk free assets. Since U.S. financial markets are fairly liquid and reasonably efficient, estimates of the required input variables are relatively reliable. In contrast, the estimation of equity capital costs for corporations based in emerging markets presents many challenges. Emerging markets are often characterized by additional risks including political risks and the risks associated with operating in markets that are less liquid and transparent than mature markets. This leads to issues in identifying appropriate and reliable measures of the risk free rate, beta and the equity risk premium. In this paper we describe five commonly used approaches to estimate the cost of equity for firms based in emerging markets and then apply these to three firms headquartered in Brazil. The results show that the approach selected can have a significant impact on the resulting estimate of the firm’s cost of equity. This case study may be of interest to practitioners and to students in financial management, investment, valuation and international finance courses.
Keywords: Management; Equity; Cost; Marketing; Finance